Wear is Your Mobile? Investigating Phone Carrying and Use Habits with a Wearable Device - Van Laerhoven, Kristof; Borazio, Marko; Burdinski, Jan Hendrik (Frontiers in ICT, 2015)
This article explores properties and suitability of mobile and wearable platforms for continuous activity recognition and monitoring. Mobile phones have become generic computing platforms, and even though they might not always be with the user, they are increasingly easy to develop for and have an unmatched variety of on-board sensors. Wearable units in contrast tend to be purpose-built, and require a certain degree of user adaptation, but they are increasingly used to do continuous sensing. We explore the trade-offs for both device types in a study that compares their sensor data and that explicitly examines how often these devices are being worn by the user. To this end, we have recorded a dataset from 51 participants, who were given a wrist-worn sensor and an app to be used on their Smartphone for two weeks continuously, totalling 638 days (or over 15300 hours) of wearable and mobile data. Results confirm findings of previous studies from North America and show that Smartphones are on average being on their user less than 23% of the time, mostly during working hours. Just as noteworthy is the high variance in Smartphone use (in carrying, interacting with, and charging the phone) among participants.